1
$\begingroup$

Let $f(t)=\sum_{k=1}^n c_k e^{ia_k t}$ and $g(t)=\sum_{k=1}^n d_k e^{ib_k t}$ be exponential polynomials with complex coefficients and having $n$ terms; and suppose they are equal in modulus: \begin{equation} |f(t)|=|g(t)| \qquad \text{for } t\in\mathbb{R} \end{equation} What does this imply about their exponent sets $A:=\{a_k\}$ and $B:=\{b_k\}$? In particular, does it follow that $A-A=B-B$ and how would you prove this?

Here's a start: $|f(t)|^2=|g(t)|^2$ is equivalent to \begin{equation} \sum_{k,j} c_k c_j^* e^{i(a_k - a_j)t} =\sum_{k,j} d_k d_j^* e^{i(b_k - b_j)t} \end{equation}

which can be written \begin{equation} \sum_l C_l \cos(A_l t+ \phi_l) = \sum_l D_l \cos(B_l t+ \psi_l) \end{equation} where the $A_l$ and $B_l$ are of the form $|a_j-a_k|$ and $|b_j-b_k|$ respectively, and appear only once in their respective sums. The desired result $A-A=B-B$ follows only if none of the coefficients $C_l$ and $D_l$ vanish.

Now, they can't all vanish of course, so the above argument at least implies the equality of some subsets of $A-A$ and $B-B$.

$\endgroup$
0
$\begingroup$

Hint. You only need to use the following fact:

If $a_1,\ldots,a_n$ are distinct real numbers, then the functions $\exp(i a_1 t),\ldots,\exp(i a_n t)$ are linearly independent over $\mathbb R$.

This can be shown inductively. For $n=1$ it is obvious. Assume that it holds for $n=k$, and $a_1,\ldots,a_k,a_{k+1}$ are distinct, and $$ c_1\exp(i a_1 t)+\cdots+c_k\exp(i a_k t) +c_{k+1}\exp(i a_{k+1} t)=0, $$ for all $t$, where $c_1,\ldots,c_{k+1}\in \mathbb R$. Then $$ c_1\exp(i (a_1-a_{k+1}) t)+\cdots+c_k\exp(i (a_k-a_{k+1}) t) +c_{k+1}=0, $$ and differentiating we obtain $$ i (a_1-a_{k+1})c_1\exp(i (a_1-a_{k+1}) t)+\cdots+i (a_k-a_{k+1})c_k\exp(i (a_k-a_{k+1}) t)=0, $$ which by the inductive hypothesis implies that $$ i (a_1-a_{k+1})c_1=\cdots=i (a_k-a_{k+1})c_{k+1}=0, $$ and since $a_j\ne a_\ell$, then $$ c_1=\cdots=c_k=0, $$ and hence $c_{k+1}=0$, as well.

| cite | improve this answer | |
$\endgroup$
  • $\begingroup$ I don't see how this is useful... For instance, |e^(it)+e^(3it)| = |1+e^(2it)| even though the consitutent functions are linearly independent. Also, please say whether you concur with the conjecture that A-A = B-B. Thanks the response. $\endgroup$ – MathManM Apr 2 '14 at 21:17
  • $\begingroup$ It can be used with the equation $$ \sum_{k,j} c_k \bar c_j \mathrm{e}^{i(a_k - a_j)t} =\sum_{k,j} d_k \bar d_j \mathrm{e}^{i(b_k - b_j)t}. $$ $\endgroup$ – Yiorgos S. Smyrlis Apr 2 '14 at 21:30
  • $\begingroup$ Okay, group like terms and rewrite this equation as \begin{equation} \sum_{l}C_l e^{i A_l t}= \sum_{l}D_l e^{i B_l t}= \end{equation} where \begin{equation}C_l = \sum_{k,j:a_k-a_j=A_l} c_k c_j^*\end{equation} and \begin{equation} D_l = \sum_{k,j:b_k-b_j=B_l} d_k d_j^*\end{equation} Linear independence implies that sets $\{a_k-a_j: C_l \neq 0\}=\{b_k-b_j: D_l \neq 0 \}$, but this is less than the desired result $A-A=B-B$ in the notation above. Please elaborate. $\endgroup$ – MathManM Apr 2 '14 at 21:41

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.